2015
DOI: 10.2147/jir.s82261
|View full text |Cite
|
Sign up to set email alerts
|

Implications of compromised zinc status on bone loss associated with chronic inflammation in C57BL/6 mice

Abstract: Compromised zinc status and chronic inflammation are independent factors that can contribute to bone loss. However, zinc’s role in regulating lymphoid and myeloid cell populations, combined with the interplay between the immune and skeletal systems raises the question as to the extent to which a low-grade inflammatory challenge in the context of marginal zinc deficiency would exacerbate bone loss. To address this question, young adult C57BL/6 male mice (n=32) were used in a 2×2 factorial design with dietary zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…2, 59 Chongwatpol P. et al, (2015) illuminated that LPS substantially decreased trabecular bone volume, lumbar vertebra bone mineral density, and the number of the vertebral bodies in the mouse model. 60…”
Section: And Probiotics Bacterial Species Has a Beneficial Function On Bone Mass Function (Table-1)mentioning
confidence: 99%
“…2, 59 Chongwatpol P. et al, (2015) illuminated that LPS substantially decreased trabecular bone volume, lumbar vertebra bone mineral density, and the number of the vertebral bodies in the mouse model. 60…”
Section: And Probiotics Bacterial Species Has a Beneficial Function On Bone Mass Function (Table-1)mentioning
confidence: 99%
“…These bacteria have the ability to release LPS, with small amounts entering the bloodstream normally through the gut epithelium [30]. Some of the previous studies showed that trabecular bone structures, bone mineral density, and bone strength were adversely affected by LPS treatment [32][33][34][35][36][37]. Therefore, inflammatory effects and genotoxic stress may occur in osteocyte cells exposed to LPS for a long time.…”
Section: Introductionmentioning
confidence: 99%